Floods and safety of establishments and installations containing hazardous substances: Conclusions on a Research Project of the German Umweltbundesamt - Fendler, Roland (Natural hazards (Dordrecht), 2008)
As a consequence of the floods in Germany in August 2002 the Umweltbundesamt (German Environment Agency) set up a research project on natural hazards and their relevance for the safety of establishments and installations containing hazardous substances, i.e. the prevention of “Natechs” (Natural hazards triggering technological accidents). The scope of the project included hazards by earthquakes and storms but the main focus was on floods. Subject of the project was the safety of establishments, installations containing substances hazardous to water according to the German Federal Water Act (e.g. chemical plants, tank farms, filling stations, heating oil tanks) and vessels for storage of extremely flammable gases (mainly LPG). The project included a survey of the flood risk management at establishments and installations in the catchment areas of the Rhine and the Elbe, a description of available flood protection and safety technology and a discussion of emergency planning requirements. Gaps in flood risk management at industrial sites and installations were identified and recommendations on policy, regulations, standards and safety management made.